The Effect of Corporate Sukuk and Sharia Mutual Funds On Economic Growth In Indonesia - Desmillasari Ramadhani Andriza; Reny Fitriana Kaban; Hidajat Sofjan Widjaja (Universitas Gorontalo, 2021)
This research aims to determine the effect of corporate sukuk and Sharia mutual funds on economic growth in Indonesia. Using quantitative method, secondary data were obtained from OJK's financial quarterly reports and Central Statistics Agency for period the 1st quarter of 2013 to the 4th quarter of 2020. The results showed that partially corporate sukuk had a positive and significant effect on economic growth Sharia mutual funds had a positive but insignificant effect to economic growth in Indonesia. However corporate sukuk and Sharia mutual funds simultaneously had a positive and significant effect on economic growth in Indonesia. Although partially Sharia mutual funds have a little effect on economic growth in Indonesia, the socialization needs to be improved so that the public will know more about Sharia mutual funds and they are interested to invest in this financial instrument.